Effects of centella asiatica extract on learning and memory of adolescent rats - Yeo, Nor Aqilah Mohd Yusuf (2017)
Centella asiatica, herbs from mackinlayoideae family, is a native to the wetlands in the tropical and subtropical region of Asia that has many beneficial effect to health. Centella asiatica is herbal plant containing phytochemicals that strongly believes has an effect on cognitive function. Learning is an acquisition and storage of information as a consequence of experience. Memory is a relatively permanent storage form of the learned information where the hippocampus is plays the most important roles in mammals in mediation of learning and the formation of new memories. Adolescence stage is the critical development period for maturation of brain processes that encompassed by changes in physical, psychological, social development, cognitive and neurotransmitter system. Specifically, the terminology of ‘adolescence’ in mammals represents the entire postnatal period, which ranges from weaning postnatal day 21 to adulthood postnatal day 60. Any alteration in this period caused by nootropics agent may bring beneficial effect to the brain especially in cognitive functions. This study investigated the effects of the extract of Centella asiatica in enhancement of learning and memory in adolescent rats by using the behavior assessments: open field test and water T-maze test. This study also examined neuronal cell morphological changes using cresyl violet and apoptosis staining. We analysed the expression of glutamate AMPA receptor (amino-3-hydroxy-5-methyl-4- -isoazole-propionic acid) subtype - GluA1 and GABA receptor (Gamma- Aminobutyric Acid) subtype – GABA A α1 using immunohistochemistry in the hippocampus of the same animals. The result showed no significant changes in